Myogenic differentiation of human myoblasts and Mesenchymal stromal cells under GDF11 on Poly-ɛ-caprolactone-collagen I-Polyethylene-nanofibers - Aijia Cai; Paul Schneider; Zeng-Ming Zheng; Justus P. Beier; Marcus Himmler; Dirk W. Schubert; Volker Weisbach; Raymund E. Horch; Andreas Arkudas (BMC Molecular and Cell Biology, 2023)
Abstract Background For the purpose of skeletal muscle engineering, primary myoblasts (Mb) and adipogenic mesenchymal stem cells (ADSC) can be co-cultured and myogenically differentiated. Electrospun composite nanofiber scaffolds represent suitable matrices for tissue engineering of skeletal muscle, combining both biocompatibility and stability Although growth differentiation factor 11 (GDF11) has been proposed as a rejuvenating circulating factor, restoring skeletal muscle function in aging mice, some studies have also described a harming effect of GDF11. Therefore, the aim of the study was to analyze the effect of GDF11 on co-cultures of Mb and ADSC on poly-ε-caprolactone (PCL)-collagen I-polyethylene oxide (PEO)-nanofibers. Results Human Mb were co-cultured with ADSC two-dimensionally (2D) as monolayers or three-dimensionally (3D) on aligned PCL-collagen I-PEO-nanofibers. Differentiation media were either serum-free with or without GDF11, or serum containing as in a conventional differentiation medium. Cell viability was higher after conventional myogenic differentiation compared to serum-free and serum-free + GDF11 differentiation as was creatine kinase activity. Immunofluorescence staining showed myosine heavy chain expression in all groups after 28 days of differentiation without any clear evidence of more or less pronounced expression in either group. Gene expression of myosine heavy chain (MYH2) increased after serum-free + GDF11 stimulation compared to serum-free stimulation alone. Conclusions This is the first study analyzing the effect of GDF11 on myogenic differentiation of Mb and ADSC co-cultures under serum-free conditions. The results of this study show that PCL-collagen I-PEO-nanofibers represent a suitable matrix for 3D myogenic differentiation of Mb and ADSC. In this context, GDF11 seems to promote myogenic differentiation of Mb and ADSC co-cultures compared to serum-free differentiation without any evidence of a harming effect.